Sulfide-based all-solid-state battery cathode active material

A lithium metal oxide core coated with niobium and tungsten shells in all-solid-state batteries addresses low conductivity and instability issues, enhancing discharge capacity and stability by reducing interfacial resistance and side reactions.

JP7612246B2Active Publication Date: 2025-01-14LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023519766
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-07
Filing Date
2022-08-30
Publication Date
2025-01-14
Estimated Expiration
2042-08-30

AI Technical Summary

Technical Problem

All-solid-state batteries using sulfide-based solid electrolytes face issues with low ionic conductivity, interfacial side reactions, and reduced discharge capacity due to the low contact area between the electrode active material and the electrolyte, as well as instability from cobalt-sulfur reactions.

Method used

A positive electrode active material for all-solid-state batteries is developed, comprising a lithium metal oxide core coated with a shell containing niobium and tungsten, which enhances lithium ion mobility and reduces side reactions by controlling the content and distribution of these elements.

Benefits of technology

The core-shell structure improves discharge performance and stability by minimizing interfacial resistance and side reactions, maintaining high discharge capacity and extending battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612246000001
    Figure 0007612246000001
  • Figure 0007612246000002
    Figure 0007612246000002
  • Figure 0007612246000003
    Figure 0007612246000003
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material for an all-solid-state battery, and the positive electrode active material contains a lithium metal oxide represented by Chemical Formula 1 as a core, which contains a high content of nickel and a certain percentage or less of cobalt, and has a shell containing niobium and tungsten on a surface of the core. This has the advantages of improving the mobility of lithium ions, reducing side reactions between the positive electrode active material and a solid electrolyte, and improving the discharge performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material for a sulfide-based all-solid-state battery.

[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0173748 dated December 7, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference. [Background technology]

[0003] An all-solid-state lithium battery is a battery that uses a sulfide-based or oxide-based solid electrolyte and can directly convert chemical energy into electrical energy by oxidizing or reducing lithium ions through the all-solid-state material.

[0004] However, although batteries using solid electrolytes have superior stability compared to conventional liquid electrolyte systems, their capacity, output, and other performances are still inferior to those of conventional liquid electrolyte systems due to the low ionic conductivity of the solid electrolyte. The reason for the low ionic conductivity in batteries using solid electrolytes is that the contact area between the electrode active material and the solid electrolyte is not as large as that of conventional liquid electrolyte systems, and the ionic conductivity of the solid electrolyte itself is low.

[0005] Specifically, all-solid-state batteries have problems such as irreversibility due to side reactions at the interface between the sulfide- or oxide-based solid electrolyte and the positive electrode during charge and discharge reactions, and a decrease in battery capacity due to interface resistance and uneven distribution of electrode charge due to space-charge layer formation.

[0006] To solve these problems, a coating technique that can passivate the surface of the positive electrode active material has been proposed. Passivation is a process that prevents the surface of any material from changing its original properties even when exposed to external conditions or stimuli. When a clean iron surface comes into contact with oxygen in the air, rust will form immediately. To prevent this, anti-rust treatment is applied to the surface.

[0007] However, despite such efforts, the charge / discharge characteristics of batteries manufactured using the same are still insufficient in many areas, and many improvements are still required.

[0008] On the other hand, as a positive electrode active material for lithium secondary batteries, lithium composite metal oxide (Li(NiCoMn)O2) basically has excellent battery characteristics, but has limitations in terms of safety, particularly thermal safety and overcharge characteristics.

[0009] As a result, there have been attempts to use lithium composite metal oxide (Li(NiCoMn)O2) as a positive electrode active material for all-solid-state batteries. However, in the case of batteries using the lithium composite metal oxide, particularly a sulfide-based solid electrolyte, the stability and performance of the positive electrode active material may be reduced due to a reaction between cobalt and sulfur. If the content of cobalt in the lithium composite metal oxide is reduced to improve this, the discharge capacity of the battery is not fully realized, resulting in a significant decrease in charge and discharge efficiency. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Korean Patent Publication No. 10-2021-0117002 Summary of the Invention [Problem to be solved by the invention]

[0011] Therefore, an object of the present invention is to provide a positive electrode active material that is excellent in the charge and discharge characteristics, particularly the discharge capacity, of a battery while using a lithium composite metal oxide containing a high content of nickel and a low content of cobalt as a positive electrode active material of a sulfide-based all-solid-state battery, and a sulfide-based all-solid-state battery containing the same. [Means for solving the problem]

[0012] To solve the above problems, In one embodiment, the present invention comprises: A core containing a lithium metal oxide represented by the following chemical formula 1; The present invention provides a positive electrode active material for an all-solid-state battery, the positive electrode active material including a shell adsorbed on the surface of the core and containing niobium (Nb) and tungsten (W).

[0013] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O u

[0014] In the above chemical formula 1, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, v, and u are 1.0≦x≦1.30, 0.7≦y<0.95, 0 <z≦0.07、0.01<w≦0.3、0≦v≦0.1、1.5≦u≦4.5である。

[0015] Here, the niobium (Nb) and tungsten (W) may be in the form of a mixture of niobium oxide particles and tungsten oxide particles; or in the form of niobium tungsten oxide particles.

[0016] The niobium (Nb) and tungsten (W) may be contained in an amount of 0.01 to 5% by weight based on the total weight of the positive electrode active material.

[0017] The niobium (Nb) may be contained in an amount of 2,500 ppm or more relative to the entire positive electrode active material, and the tungsten (W) may be contained in an amount of 6,000 ppm or less relative to the entire positive electrode active material.

[0018] The ratio (Nb / W) of the contents of niobium (Nb) and tungsten (W) contained in the shell may be 0.1 to 3.0.

[0019] The positive electrode active material may have an average particle size of 0.5 μm to 10 μm.

[0020] Moreover, the shell can be adsorbed to an area of ​​60% or more based on the total area of ​​the core.

[0021] In one embodiment, the present invention provides a method for producing a composition comprising: A step of preparing a mixture of lithium metal oxide and niobium (Nb) and tungsten (W)-containing oxide represented by the following formula 1: and heat-treating the mixture.

[0022] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O u

[0023] In the above chemical formula 1, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, v, and u are 1.0≦x≦1.30, 0.7≦y<0.95, 0 <z≦0.07、0.01<w≦0.3、0≦v≦0.1、1.5≦u≦4.5である。

[0024] Here, the niobium (Nb) and tungsten (W)-containing oxide may be contained in an amount of 0.1 to 10% by weight based on the total weight of the mixture.

[0025] The heat treatment may be performed at a temperature of 300°C to 500°C.

[0026] Moreover, in one embodiment, the present invention provides A positive electrode including the positive electrode active material according to the present invention described above; A negative electrode; and a sulfide-based solid electrolyte disposed between the positive electrode and the negative electrode.

[0027] In this case, the sulfide-based solid electrolyte may include one or more selected from the group consisting of Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and Li2S-P2S5. Effect of the Invention

[0028] The positive electrode active material for an all-solid-state battery according to the present invention contains a lithium metal oxide of Chemical Formula 1 containing a high content of nickel and a low content of cobalt as a core, and a shell containing niobium and tungsten is provided on the surface of the core. This has the advantages of improving the mobility of lithium ions, reducing side reactions between the positive electrode active material and the solid electrolyte, and improving the discharge performance of the battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] While the present invention may be modified in many ways and have many different embodiments, a specific embodiment will be described in detail.

[0030] It should be understood, however, that this is not intended to limit the invention to the particular embodiments, but rather to include all modifications, equivalents, or alternatives falling within the spirit and scope of the invention.

[0031] In the present invention, the terms "comprise" or "have" and the like are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, but are to be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0032] In addition, in the present invention, when a layer, film, region, plate, or other portion is described as being "on" another portion, this includes not only the case where it is "directly on" the other portion, but also the case where there is another portion in between. Conversely, when a layer, film, region, plate, or other portion is described as being "under" the other portion, this includes not only the case where it is "directly under" the other portion, but also the case where there is another portion in between. In addition, in the present application, being "located on" may include not only the case where it is located at the top, but also the case where it is located at the bottom.

[0033] In addition, in the present invention, "containing as a main component" means 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, or 97.5% by weight or more based on the total weight of the composition such as a slurry or the specific component, and in some cases means 100% by weight when it constitutes the entire composition or specific component.

[0034] The present invention will now be described in more detail.

[0035] <Cathode active material for all-solid-state batteries> In one embodiment, the present invention comprises: a core containing a lithium metal oxide; The present invention provides a positive electrode active material for an all-solid-state battery, the positive electrode active material including a shell adsorbed on the surface of the core and containing niobium (Nb) and tungsten (W).

[0036] The positive electrode active material according to the present invention is used in a sulfide-based all-solid-state lithium secondary battery, and has a structure in which a lithium metal oxide that exhibits electrical activity during charging and discharging of the battery is contained as a core, and particles containing both niobium (Nb) and tungsten (W) are adsorbed on the surface of the core to form a shell.

[0037] Here, the lithium metal oxide may be any lithium metal oxide that provides lithium ions by reversibly reacting during charging and discharging of a battery, without any particular limitation. Specifically, the lithium metal oxide may include a lithium metal oxide represented by the following Chemical Formula 1:

[0038] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O u

[0039] In the above chemical formula 1, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, v, and u are 1.0≦x≦1.30, 0.7≦y<0.95, 0 <z≦0.07、0.01<w≦0.3、0≦v≦0.1、1.5≦u≦4.5である。

[0040] The lithium metal oxide represented by the above formula 1 is an oxide containing lithium and a transition metal, and among the transition metals, nickel may be contained in a high content and cobalt may be contained below a certain level. Specifically, the lithium metal oxide may be nickel (Ni), cobalt (Co), manganese (Mn) and an additional metal (M 1 ), nickel may be contained at 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, or 90 mol% or more, and cobalt (Co) may be contained at 7 mol% or less, 6 mol% or less, 5 mol% or less, or 3 mol% or less.

[0041] As an example, the lithium metal oxide is LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.8 Co 0.05 Mn 0.15 O2, LiNi 0.7 Co 0.05 Mn 0.25 O2, LiNi 0.8 Co 0.05 Mn 0.1 Al 0.05 O2, LiNi 0.7 Co 0.05 Mn 0.15 Al 0.1 O2, LiNi 0.7 Co 0.05 Mn 0.2 Al 0.05 O2 and LiNi 0.8 Co 0.05 Mn 0.1 Al 0.05 O2. The lithium metal oxide is excellent in improving the charge and discharge capacity of the battery.

[0042] In addition, the core has a structure in which a shell containing niobium (Nb) and tungsten (W) is adsorbed on the surface, which reduces the interfacial resistance between the positive electrode active material and the solid electrolyte, improves the ability to resist side reactions between the positive electrode active material and the solid electrolyte, and suppresses the loss of lithium ions, thereby improving the electrical performance of the battery.

[0043] Specifically, the lithium metal oxide represented by Chemical Formula 1 has a layered structure and is characterized by large contraction and expansion due to charging and discharging of a secondary battery. Therefore, when the lithium metal oxide is contained in the core as a positive electrode active material, the core is repeatedly induced to contract and expand due to charging and discharging of the battery, causing the shell to detach from the core surface, which increases the resistance of the electrode, while inducing a crack phenomenon at the contact surface at the interface between the active material and the electrolyte, resulting in a limited reduction in battery life. However, the shell according to the present invention contains niobium (Nb) and tungsten (W), and when the lithium metal oxide represented by Chemical Formula 1 is adsorbed on the core, the shell does not detach due to the contraction and expansion of the core due to charging and discharging of the battery, and the contact surface crack phenomenon at the interface between the active material and the electrolyte can be significantly improved.

[0044] In this case, the shell may contain niobium (Nb) and tungsten (W) in a form in which niobium oxide particles and tungsten oxide particles are mixed, or in a form in which niobium oxide particles and tungsten oxide particles are mixed. The niobium oxide particles may include NbO, NbO2, Nb2O5, Nb2O6, etc., and the tungsten oxide may include WO2, WO3, W2O3, W 20 O 58 , W 24 O 70 , W 18 O 49 The niobium tungsten oxide particles may include NbWO6, Nb2O5 / WO3, Nb8W9O 47 , NbW 13 O 47 , Nb7W 10 O 47 , Nb 14 W3O 44 , Nb 16 W5O 55 , and Nb 18 W 16 O 93 etc. may be included.

[0045] As an example, the shell may have a composition including Nb2O6 particles and WO3 particles in a uniform mixture, in which case the niobium oxide and tungsten oxide have the advantages of excellent electrical properties and high thermodynamic state stability.

[0046] As another example, the shell may include NbWO6 particles. In this case, the positive electrode active material has excellent electrical properties, high thermodynamic state stability, and can effectively suppress side reactions between the positive electrode active material and the sulfide-based solid electrolyte during charging and discharging of the battery, and has the advantages of good workability.

[0047] The niobium (Nb) and tungsten (W) contained in the shell may be contained in an amount of 0.01 to 5 wt % relative to the total weight of the positive electrode active material, and specifically, may be contained in an amount of 0.01 to 3 wt %, 0.01 to 2 wt %, 1 to 2.5 wt %, 1.5 to 2.3 wt %, 1.8 to 2.4 wt %, 0.05 to 1.9 wt %, 0.1 to 1.5 wt %, 0.1 to 0.9 wt %, or 0.8 to 1.8 wt %.

[0048] By controlling the contents of niobium (Nb) and tungsten (W) contained in the shell within the above ranges, the present invention can impart excellent electrical conductivity to the surface of the positive electrode active material during charging and discharging of the battery, and can impart insulating properties to the shell when the electrochemical action of the battery is not occurring (for example, when charging and discharging are not performed), thereby preventing the battery from self-discharging.

[0049] The shell may also contain niobium (Nb) and tungsten (W) at specific concentrations and / or content ratios.

[0050] As an example, the niobium (Nb) may be contained in an amount of 2,500 ppm or more relative to the entire positive electrode active material, and the tungsten (W) may be contained in an amount of 6,000 ppm or less relative to the entire positive electrode active material.

[0051] Specifically, the niobium (Nb) may be contained at a concentration of 2,800 ppm or more, 3,000 ppm or more, 3,200 ppm or more, 3,500 ppm or more, 4,000 ppm or more, 2,500 to 6,000 ppm, 2,500 to 3,500 ppm, or 2,500 to 3,200 ppm relative to the entire positive electrode active material, and the tungsten (W) may be contained at a concentration of 5,500 ppm or less, 5,000 ppm or less, 4,500 ppm or less, 4,000 ppm or less, 2,000 to 6,000 ppm, 2,000 to 5,500 ppm, 2,000 to 5,000 ppm, 2,000 to 4,500 ppm, or 2,000 to 4,000 ppm relative to the entire positive electrode active material.

[0052] As another example, the ratio (Nb / W) of the niobium (Nb) and tungsten (W) contained in the shell may be 0.1 to 3.0, and more specifically, it may be 0.5 to 3.0, 0.5 to 2.5, 0.8 to 1.9, 1.1 to 1.8, 1.5 to 2.5, 1.9 to 2.4, or 1.2 to 2.4.

[0053] The present invention is capable of minimizing the reaction between cobalt (Co) contained in the core and sulfur (S) contained in the solid electrolyte by controlling the concentration and / or content ratio of niobium (Nb) and tungsten (W) contained in the shell of the positive electrode active material within a specific range, thereby improving the charge / discharge performance, specifically, the discharge capacity, of the positive electrode active material.

[0054] The positive electrode active material may have an average particle size of 0.5 μm to 10 μm, and in this case, the particles constituting the shell, i.e., niobium oxide particles and tungsten oxide particles; or niobium tungsten oxide particles, may have a particle form having an average particle size of 0.1 nm to 40 nm.

[0055] More specifically, the positive electrode active material may have an average particle size of 0.5 μm to 8 μm, 0.5 μm to 6 μm, 0.5 μm to 5 μm, 0.5 μm to 4 μm, 5 μm to 9 μm, 1 μm to 4 μm, 2 μm to 4 μm, 4 μm to 7 μm, 0.5 μm to 3 μm, 1 μm to 3 μm, or 3 μm to 8 μm, and the average particle size of the particles contained in the shell of the positive electrode active material may be 0.1 nm to 30 nm, 0.1 nm to 20 nm, 0.1 nm to 10 nm, 5 nm to 30 nm, 5 nm to 20 nm, 8 nm to 15 nm, or 4 nm to 15 nm.

[0056] In the present invention, by controlling the average particle size of the positive electrode active material within the above range, the electrode activity of the positive electrode can be further improved, and by controlling the average particle size of the particles constituting the shell within the above range, the decrease in the electrical activity of the lithium metal oxide core can be minimized, side reactions at the interface with the solid electrolyte can be effectively suppressed, and cracks that may occur on the surface of the positive electrode active material can be prevented.

[0057] Moreover, the shell containing niobium (Nb) and tungsten (W) can surround 60% or more of the total surface of the core containing lithium metal oxide, and the particles constituting the shell may have a structure in which they are physically uniformly adsorbed to the surface of the core containing lithium metal oxide, not by chemical bonding. Specifically, the area of ​​the particles constituting the shell adsorbed to the core may be 60% or more of the core surface area, more specifically, 70% or more, 80% or more, 90% or more, 95% or more, or 98% or more. The present invention can effectively suppress side reactions between the positive electrode active material and the solid electrolyte without using excessive amounts of niobium (Nb) and tungsten (W) by controlling the area of ​​the shell containing lithium metal oxide adsorbed to the surface of the core to the above ratio.

[0058] The positive electrode active material for an all-solid-state battery according to the present invention has the above-mentioned configuration, and thus has the advantages of improving the mobility of lithium ions, reducing side reactions between the positive electrode active material and the solid electrolyte, and improving the discharge performance of the battery.

[0059] <Method of manufacturing positive electrode active material for all-solid-state batteries> In one embodiment, the present invention provides a method for producing a composition comprising: A step of preparing a mixture of lithium metal oxide and niobium (Nb) and tungsten (W)-containing oxide represented by the following formula 1: and heat-treating the mixture.

[0060] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O u

[0061] In the above chemical formula 1, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, v, and u are 1.0≦x≦1.30, 0.7≦y<0.95, 0 <z≦0.07、0.01<w≦0.3、0≦v≦0.1、1.5≦u≦4.5である。

[0062] The method for producing a positive electrode active material for an all-solid-state battery according to the present invention relates to the method for producing a positive electrode active material for an all-solid-state battery according to the present invention described above, and can be carried out by producing a mixture of a lithium metal oxide represented by Chemical Formula 1 forming a core and a niobium (Nb)- and tungsten (W)-containing oxide forming a shell, and heat-treating the mixture.

[0063] In this case, the step of preparing a mixture by mixing the lithium metal oxide with the niobium (Nb) and tungsten (W)-containing oxide may be performed using a dry mixer, a stirrer, a shaker such as an orbital shaker, a mortar mixer, a planetary ball mill, or a milling machine that are used in the art to mix powders of metal compounds, but is not limited thereto.

[0064] As an example, the step of preparing the mixture may be carried out using a planetary ball mill at a speed of 50-500 rpm for 0.1-10 hours with a power of 1-100 kWh / 1 kg of the mixture.

[0065] As another example, the step of preparing the mixture may be carried out by mixing using a shaker for 1 to 10 hours, specifically, for 2 to 8 hours.

[0066] In the mixture, the lithium metal oxide represented by Chemical Formula 1 may be an oxide containing a transition metal together with lithium, and in particular, may be an oxide containing a high content of nickel among the transition metals. As an example, the lithium metal oxide is LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.8 Co 0.05 Mn 0.15 O2, LiNi 0.7 Co 0.05 Mn 0.25 O2, LiNi 0.8 Co 0.05 Mn 0.1 Al 0.05 O2, LiNi 0.7 Co 0.05 Mn 0.15 Al 0.1 O2, LiNi 0.7 Co 0.05 Mn 0.2 Al 0.05 O2 and LiNi 0.8 Co 0.05 Mn 0.1 Al 0.05 O2.

[0067] The niobium (Nb) and tungsten (W) containing particles may also have niobium (Nb) and tungsten (W) in the form of mixed niobium oxide particles and tungsten oxide particles; or niobium tungsten oxide particles.

[0068] The niobium oxide particles may include NbO, NbO2, Nb2O5, Nb2O6, etc., and the tungsten oxide may include WO2, WO3, W2O3, W 20 O 58 , W 24 O 70 , W 18 O 49 The niobium tungsten oxide particles may include NbWO6, Nb2O5 / WO3, Nb8W9O 47 , NbW 13 O 47 , Nb7W 10 O 47 , Nb 14 W3O 44 , Nb 16 W5O 55 , and Nb 18 W 16 O 93 etc. may be included.

[0069] As an example, the shell may have a composition including Nb2O6 particles and WO3 particles in a uniform mixture, in which case the niobium oxide and tungsten oxide have the advantages of excellent electrical properties and high thermodynamic state stability.

[0070] As another example, the shell may include NbWO6 particles. In this case, the positive electrode active material has excellent electrical properties, high thermodynamic state stability, and can effectively suppress side reactions between the positive electrode active material and the sulfide-based solid electrolyte during charging and discharging of the battery, and has the advantages of good workability.

[0071] The mixture may contain 0.01 to 5 wt % of a niobium (Nb) and tungsten (W)-containing oxide relative to the total weight of the mixture, specifically, 0.01 to 3 wt %, 0.01 to 2 wt %, 1 to 2.5 wt %, 1.5 to 2.3 wt %, 1.8 to 2.4 wt %, 0.05 to 1.9 wt %, 0.1 to 1.5 wt %, 0.1 to 0.9 wt %, or 0.8 to 1.8 wt %.

[0072] The niobium (Nb) and tungsten (W)-containing oxide may contain niobium (Nb) and tungsten (W) at specific concentrations and / or content ratios, respectively.

[0073] As an example, the niobium (Nb) may be contained in an amount of 2,500 ppm or more relative to the total mixture, and the tungsten (W) may be contained in an amount of 6,000 ppm or less relative to the total mixture.

[0074] Specifically, the niobium (Nb) may be contained in a concentration of 2,800 ppm or more, 3,000 ppm or more, 3,200 ppm or more, 3,500 ppm or more, 4,000 ppm or more, 2,500 to 6,000 ppm, 2,500 to 3,500 ppm, or 2,500 to 3,200 ppm relative to the entire mixture, and the tungsten (W) may be contained in a concentration of 5,500 ppm or less, 5,000 ppm or less, 4,500 ppm or less, 4,000 ppm or less, 2,000 to 6,000 ppm, 2,000 to 5,500 ppm, 2,000 to 5,000 ppm, 2,000 to 4,500 ppm, or 2,000 to 4,000 ppm relative to the entire mixture.

[0075] As another example, the ratio (Nb / W) of the niobium (Nb) and tungsten (W) contained in the mixture may be 0.1 to 3.0, and more specifically, may be 0.5 to 3.0, 0.5 to 2.5, 0.8 to 1.9, 1.1 to 1.8, 1.5 to 2.5, 1.9 to 2.4, or 1.2 to 2.4.

[0076] The present invention controls the content ratio and / or concentration of niobium (Nb) and tungsten (W) contained in the niobium (Nb) and tungsten (W)-containing oxide mixed with the lithium metal oxide as the core within a specific range, thereby minimizing the reaction between cobalt (Co) contained in the core and sulfur (S) contained in the solid electrolyte, thereby improving the charge / discharge performance of the positive electrode active material, specifically, the discharge capacity.

[0077] In addition, the step of heat-treating the mixture containing the lithium metal oxide and the niobium (Nb)- and tungsten (W)-containing oxide can be said to be a step of fixing the niobium (Nb)- and tungsten (W)-containing oxide physically adsorbed on the surface of the lithium metal oxide as the core.

[0078] In this case, the heat treatment temperature may be 300°C or higher, and may be preferably 300°C to 480°C, 350°C to 500°C, 400°C to 500°C, or 420°C to 480°C.

[0079] In the present invention, by adjusting the heat treatment temperature of the mixture containing the lithium metal oxide and the niobium (Nb) and tungsten (W)-containing oxide within the above range, the niobium (Nb) and tungsten (W)-containing oxide can be easily fixed to the surface of the lithium metal oxide as the core without side reactions.

[0080] The method for producing a positive electrode active material for an all-solid-state battery according to the present invention has an advantage that the production efficiency of a positive electrode active material having a core-shell structure is excellent since a shell in which a niobium (Nb) and tungsten (W)-containing oxide is uniformly coated on the surface of a core containing a lithium metal oxide without aggregation can be formed.

[0081] <All-solid-state lithium secondary battery> Moreover, in one embodiment, the present invention provides A positive electrode including the positive electrode active material according to the present invention described above; A negative electrode; and a sulfide-based solid electrolyte disposed between the positive electrode and the negative electrode.

[0082] The all-solid-state lithium secondary battery according to the present invention includes a cathode containing the above-mentioned cathode active material of the present invention, and not only is there a significantly reduced void phenomenon occurring at the interface between the cathode active material and the solid electrolyte, but side reactions are also suppressed, so that the lithium ion mobility of the electrode is excellent, and in particular, the discharge performance of the battery is improved.

[0083] In this case, the positive electrode may have a structure in which a positive electrode mixture layer containing the above-mentioned positive electrode active material of the present invention is formed on a positive electrode current collector.

[0084] The positive electrode current collector is not particularly limited as long as it has high conductivity without inducing a chemical change in the battery, and may include, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like.

[0085] The positive electrode mixture layer contains a positive electrode active material, a conductive material, a binder, and a solid electrolyte, and may further contain an additive in some cases.

[0086] Here, the positive electrode active material may have a structure including a core containing a lithium metal oxide represented by the following chemical formula 1, and a shell adsorbed to the surface of the core and containing niobium (Nb) and tungsten (W).

[0087] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O u

[0088] In the above chemical formula 1, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, v, and u are 1.0≦x≦1.30, 0.7≦y<0.95, 0 <z≦0.07、0.01<w≦0.3、0≦v≦0.1、1.5≦u≦4.5である。

[0089] The lithium metal oxide may be any compound represented by Chemical Formula 1 without any particular limitation. Specifically, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.8 Co 0.05 Mn 0.15 O2, LiNi 0.7 Co 0.05 Mn 0.25 O2, LiNi 0.8 Co 0.05 Mn 0.1 Al 0.05 O2, LiNi 0.7 Co 0.05 Mn 0.15 Al 0.1 O2, LiNi 0.7 Co 0.05 Mn 0.2 Al 0.05 O2 and LiNi 0.8 Co 0.05 Mn 0.1 Al 0.05 O2.

[0090] In this case, the shell may have niobium (Nb) and tungsten (W) in the form of a mixture of niobium oxide particles and tungsten oxide particles; or in the form of niobium tungsten oxide particles. The niobium oxide particles may include NbO, NbO2, Nb2O5, Nb2O6, etc., and the tungsten oxide may include WO2, WO3, W2O3, W 20 O 58 , W 24 O 70 , W 18 O 49 The niobium tungsten oxide particles may include NbWO6, Nb2O5 / WO3, Nb8W9O 47 , NbW 13 O 47 , Nb7W 10 O 47 , Nb 14 W3O 44 , Nb 16 W5O 55 , and Nb 18 W 16 O93 etc. may be included.

[0091] As an example, the shell may have a composition including Nb2O6 particles and WO3 particles in a uniform mixture, in which case the niobium oxide and tungsten oxide have the advantages of excellent electrical properties and high thermodynamic state stability.

[0092] As another example, the shell may include NbWO6 particles. In this case, the positive electrode active material has excellent electrical properties, high thermodynamic state stability, and can effectively suppress side reactions between the positive electrode active material and the sulfide-based solid electrolyte during charging and discharging of the battery, and has the advantages of good workability.

[0093] The niobium (Nb) and tungsten (W) contained in the shell may be contained in an amount of 0.01 to 5 wt % relative to the total weight of the positive electrode active material, and specifically, may be contained in an amount of 0.01 to 3 wt %, 0.01 to 2 wt %, 1 to 2.5 wt %, 1.5 to 2.3 wt %, 1.8 to 2.4 wt %, 0.05 to 1.9 wt %, 0.1 to 1.5 wt %, 0.1 to 0.9 wt %, or 0.8 to 1.8 wt %.

[0094] By controlling the contents of niobium (Nb) and tungsten (W) contained in the shell within the above ranges, the present invention can impart excellent electrical conductivity to the surface of the positive electrode active material during charging and discharging of the battery, and can impart insulating properties to the shell when the electrochemical action of the battery is not occurring (for example, when charging and discharging are not performed), thereby preventing the battery from self-discharging.

[0095] The shell may also contain niobium (Nb) and tungsten (W) at specific concentrations and / or content ratios.

[0096] As an example, the niobium (Nb) may be contained in an amount of 2,500 ppm or more relative to the entire positive electrode active material, and the tungsten (W) may be contained in an amount of 6,000 ppm or less relative to the entire positive electrode active material.

[0097] Specifically, the niobium (Nb) may be contained at a concentration of 2,800 ppm or more, 3,000 ppm or more, 3,200 ppm or more, 3,500 ppm or more, 4,000 ppm or more, 2,500 to 6,000 ppm, 2,500 to 3,500 ppm, or 2,500 to 3,200 ppm relative to the entire positive electrode active material, and the tungsten (W) may be contained at a concentration of 5,500 ppm or less, 5,000 ppm or less, 4,500 ppm or less, 4,000 ppm or less, 2,000 to 6,000 ppm, 2,000 to 5,500 ppm, 2,000 to 5,000 ppm, 2,000 to 4,500 ppm, or 2,000 to 4,000 ppm relative to the entire positive electrode active material.

[0098] As another example, the ratio (Nb / W) of the niobium (Nb) and tungsten (W) contained in the shell may be 0.1 to 3.0, and more specifically, it may be 0.5 to 3.0, 0.5 to 2.5, 0.8 to 1.9, 1.1 to 1.8, 1.5 to 2.5, 1.9 to 2.4, or 1.2 to 2.4.

[0099] The present invention is capable of minimizing the reaction between cobalt (Co) contained in the core and sulfur (S) contained in the solid electrolyte by controlling the content ratio and / or concentration of niobium (Nb) and tungsten (W) contained in the shell of the positive electrode active material within a specific range, thereby improving the charge / discharge performance, specifically, the discharge capacity, of the positive electrode active material.

[0100] In addition, the conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery. Specifically, graphite, carbon-based materials, metal powder or metal fiber, needle-like or dendritic conductive whiskers, conductive metal oxides, conductive polymers, and any one or mixture of these can be used. More specifically, examples of the conductive material include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; needle-shaped or dendritic conductive whiskers such as zinc oxide whiskers, calcium carbonate whiskers, titanium oxide whiskers, silicon oxide whiskers, silicon carbide whiskers, aluminum borate whiskers, magnesium borate whiskers, potassium titanate whiskers, silicon nitride whiskers, silicon carbide whiskers, and alumina whiskers; conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and a mixture of any one or more of these may be used.

[0101] The positive electrode binder is any one selected from the group consisting of N,N-bis[3-(triethoxysilyl)propyl]urea, polyethylene oxide (PEO), poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-co-HFP), or a mixture of two or more of these, N,N-bis[3-(triethoxysilyl)propyl]urea, polyethylene oxide (PEO), poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-co-HFP), acrylonitrile, The rubber may be any one selected from the group consisting of conjugated diene rubber latexes such as styrene butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), methyl methacrylate butadiene rubber (MBR), butadiene rubber (BR), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers, or a mixture of two or more of these.

[0102] The negative electrode may have a structure in which a negative electrode mixture layer containing a negative electrode active material is formed on a negative electrode current collector.

[0103] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing a chemical change in the battery, and may include, for example, stainless steel, copper, nickel, titanium, baked carbon, or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like.

[0104] The negative electrode mixture layer contains a negative electrode active material, a conductive material, a binder, and a solid electrolyte, and may further contain an additive in some cases.

[0105] At this time, the negative electrode active material can be one selected from the group consisting of lithium metal, lithium alloy, lithium metal composite oxide, lithium-containing titanium composite oxide (LTO), and combinations thereof. Here, as the lithium alloy, an alloy composed of lithium and at least one metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Ba, Ra, Al, and Sn can be used. Further, the lithium metal composite oxide is any one metal (Me) oxide (MeOx) selected from the group consisting of lithium and Si, Sn, Zn, Mg, Cd, Ce, Ni, and Fe, and as an example, it may be LixFe2O3 (0 < x ≦ 1) or LixWO2 (0 < x ≦ 1).

[0106] In addition, as the negative electrode active material, metal composite oxides such as SnxMe1-xMe’yOz (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1, 1 ≦ y ≦ 3, 1 ≦ z ≦ 8) can be used; oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5 can be used, and carbon-based negative electrode active materials such as crystalline carbon, amorphous carbon, or carbon composites can be used alone or in combination of two or more.

[0107] In addition, examples of the conductive material include nickel powder, cobalt oxide, titanium oxide, carbon, etc. Examples of carbon include any one selected from the group consisting of ketjen black, acetylene black, furnace black, graphite, carbon fiber, and fullerene, or one or more of these.

[0108] The negative electrode binder is any one selected from the group consisting of N,N-bis[3-(triethoxysilyl)propyl]urea, polyethylene oxide (PEO), poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-co-HFP), or a mixture of two or more of these, N,N-bis[3-(triethoxysilyl)propyl]urea, polyethylene oxide (PEO), poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-co-HFP), styrene The rubber may be any one selected from the group consisting of conjugated diene rubber latexes such as butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), methyl methacrylate butadiene rubber (MBR), butadiene rubber (BR), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers, or a mixture of two or more of these.

[0109] Moreover, the solid electrolyte contains sulfide-based particles, and the sulfide-based particles may be those commonly used in the art as electrolytes for sulfide-based all-solid-state batteries. Specifically, one or more amorphous solid electrolytes selected from the group consisting of Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and Li2S-P2S5 may be used.

[0110] The sulfide particles may have an average particle size of 0.1 μm to 50 μm, specifically, 0.1 μm to 10 μm. By controlling the average particle size of the sulfide particles constituting the solid electrolyte within the above range, the present invention can increase the porosity of the solid electrolyte and improve the problem of reduced battery capacity.

[0111] The present invention will now be described in more detail with reference to examples and experimental examples. However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.

[0112] <Examples 1 to 3. Production of positive electrode active material for sulfide-based all-solid-state battery> LiNi with an average grain size of 5±0.1μm 0.81 Co 0.05 Mn 0.12 Al 0.02 Niobium tungsten oxide (NbWO6) with an average particle size of 20±5 nm was added to the ball mill jar and ball milled at a speed of 200±50 rpm and a power of 10 kWh / 1 kg for 1 hour to obtain LiNi 0.81 Co 0.05 Mn 0.12 Al 0.02 A mixture in which O2 and niobium tungsten oxide (NbWO6) were uniformly mixed was obtained. At this time, the total content of niobium (Nb) and tungsten (W) contained in the mixture; and the content ratio of niobium (Nb) and tungsten (W) are as shown in Table 1 below.

[0113] The mixture was transferred to an oven and then heat-treated at 450±10°C for 2 hours to obtain LiNi as the core. 0.81 Co 0.05 Mn 0.12 Al 0.02 A positive electrode active material (average particle size: 5±0.2 μm) was obtained in which the surface of O2 was uniformly coated with niobium tungsten oxide (NbWO6).

[0114] [Table 1]

[0115] <Comparative Examples 1 to 3. Production of cathode active material for sulfide-based all-solid-state battery> The same procedure as in Example 1 was carried out, except that the shell components shown in Table 2 below were used instead of niobium tungsten oxide (NbWO6), to obtain LiNi as a core. 0.81 Co 0.05 Mn 0.12 Al 0.02 A positive electrode active material (average particle size: 5±0.2 μm) was obtained in which a shell was formed on the surface of O2.

[0116] [Table 2]

[0117] <Examples 4 to 6 and Comparative Examples 4 to 6. Production of sulfide-based all-solid-state batteries> Using each of the positive electrode active materials produced in Examples 1 to 3 and Comparative Examples 1 to 3, sulfide-based all-solid-state batteries were produced.

[0118] Specifically, the positive electrode active material produced in each of the examples and comparative examples was mixed in a weight ratio of 80:15:3:2, sulfide-based solid electrolyte (Li2S-P2S5): conductive material (carbon black): binder (PVDF), and this was coated on an aluminum thin plate (thickness: 40 μm) and rolled at room temperature to prepare a positive electrode.

[0119] Separately, a lithium metal (Li) thin plate (thickness: 40 μm) was prepared as the negative electrode. A solid electrolyte membrane (70 μm, 2.8 × 10 -3 A sulfide-based all-solid-state battery was manufactured using a lithium-ion battery (Li10SnP2S12) as an intermediary.

[0120] [Table 3]

[0121] <Experimental Example> In order to evaluate the characteristics of the sulfide-based all-solid-state battery positive electrode active material according to the present invention, the following experiment was carried out.

[0122] a) Analysis of the cross-sectional structure of the positive electrode composite layer The sulfide-based all-solid-state batteries manufactured in Examples 4 to 6 and Comparative Examples 4 to 6 were prepared in a non-standby state, and their life spans were extended under conditions of room temperature (25±1°C), 3.0 to 4.25 V, and 0.1 C. Then, each battery was disassembled, and a scanning electron microscope (SEM) analysis was performed on the composite layer of the positive electrode.

[0123] As a result, the battery of the embodiment according to the present invention has a lithium metal oxide (LiNi 0.8 Co 0.1 Mn 0.1 It was confirmed that the niobium (Nb) and tungsten (W)-containing shell was uniformly adsorbed on the surface of the lithium metal oxide (CuO2). This means that the void phenomenon that occurs at the interface between the lithium metal oxide contained in the core and the sulfide-based solid electrolyte was prevented, and side reactions were suppressed.

[0124] On the other hand, the comparative battery has a lithium metal oxide (LiNi 0.8 Co 0.1 Mn 0.1 It was confirmed that cracks had occurred between the oxide (O2) and the sulfide-based solid electrolyte.

[0125] From these results, it can be seen that the cathode active material of the sulfide-based all-solid-state battery according to the present invention has a shell containing niobium and tungsten uniformly adsorbed on the surface of the core containing lithium metal oxide, thereby preventing the occurrence of a void phenomenon and side reactions between the lithium metal oxide of the core and the solid electrolyte.

[0126] B) Battery performance evaluation The sulfide-based all-solid-state batteries produced in Examples 4 to 6 and Comparative Examples 4 to 6 were fixed in a jig in a chamber at 25° C., and initial charging and discharging were performed under the condition of 0.1 C to measure the initial charging capacity and initial discharging capacity, from which the charging and discharging efficiency was calculated. At this time, the charging was performed by a constant current charging (CCC) method, and c / o was controlled to 0.05 C.

[0127] Next, the discharge capacity was measured by charging and discharging the secondary battery twice at 25° C., and each charge was performed at a current density of 0.1 C, and each discharge was measured by adjusting the current density to 0.1 C and 1 C. From the measurement results, the ratio of the discharge capacity at 1 C to the discharge capacity at 0.1 C (1 C / 0.1 C) was obtained, and the results are shown in Table 4 below.

[0128] [Table 4]

[0129] As shown in Table 4 above, the positive electrode active material for a sulfide-based all-solid-state battery of the embodiment has a structure in which a shell containing niobium (Nb) and tungsten (W) is adsorbed on the surface of a core containing lithium metal oxide, and it has been confirmed that the positive electrode active material has excellent initial charge / discharge capacity and a high ratio of the discharge capacity at 1C to the discharge capacity at 0.1C (1C / 0.1C) of 70% or more.

[0130] This means that even if the positive electrode active material of the present invention contains a high content of nickel in the core, there is little cracking at the interface between the positive electrode active material and the solid electrolyte, there is little side reaction with the electrolyte due to the cobalt contained in the core, and the electrode resistance is low.

[0131] From these results, it can be seen that the cathode active material for a sulfide-based all-solid-state battery according to the present invention can prevent an increase in electrode resistance due to charge and discharge at the interface between the cathode active material and the solid electrolyte, thereby improving the life of the battery.

[0132] Although the present invention has been described above with reference to preferred embodiments, it will be understood that a person skilled in the art or having ordinary knowledge in the art can make various modifications and variations to the present invention without departing from the spirit and technical scope of the present invention as described in the claims below.

[0133] Therefore, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification, but should be defined by the claims.

Claims

1. A core containing a lithium metal oxide represented by the following chemical formula 1; A positive electrode active material for a sulfide-based all-solid-state battery comprising: a shell adsorbed on a surface of the core and containing niobium (Nb) and tungsten (W); [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O u In the above Chemical Formula 1, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, v, and u are each within the ranges of 1.0≦x≦1.30, 0.7≦y<0.95, 0<z≦0.07, 0.01<w≦0.3, 0≦v≦0.1, and 1.5≦u≦4.5, Niobium (Nb) and tungsten (W) A mixture of niobium oxide and tungsten oxide particles; or It has the form of niobium tungsten oxide particles, A positive electrode active material for a sulfide-based all-solid-state battery, comprising niobium oxide particles and tungsten oxide particles; or the niobium tungsten oxide particles have an average particle size of 0.1 nm to 40 nm.

2. The positive electrode active material for a sulfide-based all-solid-state battery according to claim 1, wherein niobium (Nb) and tungsten (W) are contained in an amount of 0.01 to 5% by weight based on the total weight of the positive electrode active material.

3. Niobium (Nb) is contained in an amount of 2,500 ppm or more based on the total positive electrode active material, The positive electrode active material for a sulfide-based all-solid-state battery according to claim 1, wherein tungsten (W) is contained in an amount of 6,000 ppm or less based on the entire positive electrode active material.

4. The positive electrode active material for a sulfide-based all-solid-state battery according to claim 1, wherein the content ratio (Nb / W) of niobium (Nb) and tungsten (W) is 0.1 to 3.

0.

5. The cathode active material for a sulfide-based all-solid-state battery according to claim 1, wherein the average particle size of the cathode active material is 0.5 μm to 10 μm.

6. The positive electrode active material for a sulfide-based all-solid-state battery according to claim 1 , wherein the shell is adsorbed to an area of ​​60% or more of the total area of ​​the core.

7. Preparing a mixture of lithium metal oxide and niobium (Nb) and tungsten (W)-containing oxide represented by the following formula 1: The method for producing a positive electrode active material for a sulfide-based all-solid-state battery according to claim 1, further comprising: [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O u In the above Chemical Formula 1, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; wherein x, y, z, w, v, and u are 1.0≦x≦1.30, 0.7≦y<0.95, 0<z≦0.07, 0.01<w≦0.3, 0≦v≦0.1, and 1.5≦u≦4.5, respectively.

8. The method for producing a positive electrode active material for a sulfide-based all-solid-state battery according to claim 7, wherein the niobium (Nb) and tungsten (W)-containing oxide is contained in an amount of 0.1 to 10% by weight based on the total weight of the mixture.

9. The method for producing a positive electrode active material for a sulfide-based all-solid-state battery according to claim 7, wherein the heat treatment is performed at 300°C to 500°C.

10. A positive electrode comprising the positive electrode active material according to claim 1; A negative electrode; and a sulfide-based solid electrolyte disposed between the positive electrode and the negative electrode.

11. The sulfide-based solid electrolyte is Li 2 S-SiS 2 , LiI-Li 2 S-SiS 2 , LiI-Li 2 S-P 2 S 5 , LiI-Li 2 S-B 2 S 3 , Li 3 P.O. 4 -Li 2 S-Si 2 S., Li. 3 P.O. 4 -Li 2 S-SiS 2 , LiPO 4 -Li 2 S-SiS, LiI-Li 2 S-P 2 O 5 , LiI-Li 3 P.O. 4 -P 2 S 5 , and Li 2 S-P 2 S 5 The all-solid-state lithium secondary battery according to claim 10, comprising one or more selected from the group consisting of:

Citation Information

Patent Citations

  • Cathode active material for non-aqueous secondary battery and manufacturing method for the same

    JP2015201388A

  • Positive electrode active material for lithium ion battery, method for manufacturing the same, positive electrode for lithium ion battery and lithium ion battery

    JP2019139862A

  • Cathode for all-solid secondary battery and all-solid secondary battery including the same

    JP2021150286A

  • Positive active material for all solid secondary battery, and all solid secondary battery including the same

    KR1020210117002A